Pengaruh E-Service Quality, Customer Trust Dan Online Customer ReviewTerhadap Customer Loyalty Pengguna Aplikasi Shopee (Studi Kasus PadaMahasiswa Program Sarjana Universitas An Nuur Angkatan 2019/2020) - Dwi Ayu Istiqomah; Fariha azzahra (LPPM Universitas An Nuur, 2023)
Background : In the digital era, An Nuur students prefer to do practical and instant activities, one of which is shopping online via the Shopee application. Efforts to increase customer loyalty can be done through the e-service quality provided. Apart from that, Shopee also needs to convince consumers through customer trust when making a purchase that their expectations of obtaining a product or service are met. Consumers can take advantage of online customer reviews to help determine what products to buy. Purpose: This research aims to determine the influence of e-service quality, customer trust and online customer reviews on customer loyalty of application users among An Nuur University Undergraduate Program students Class of 2019/2020 Methods: The research carried out uses a type of quantitative research which aims to test predetermined hypotheses. Meanwhile, the sampling method used census techniques for 99 respondents. Then the data obtained was analyzed using the Partial Least Square (PLS) statistical analysis technique. Conclusion: So, e-service quality and customer trust play a role in increasing customer loyalty. Suggestion: There are still many limitations in this research and need to be further developed for future research agendas. The scope of this research is only within the scope of An Nuur University so its scope is not broad enough because it only focuses on one place, so you can add a population and sample with a wider coverage, such as the community in the Grobogan district. Apart from that, further research can add related variables to increase customer loyalty.